ENDS use among college students: Salivary biomarkers and persistent cough. (September 2020) - Ashford, Kristin; McCubbin, Andrea; Rayens, Mary Kay; Wiggins, Amanda; Dougherty, Kylie; Sturgill, Jamie; Ickes, Melinda
Highlights: This is the first study to investigate cytokine levels among emerging adults using ENDS. Interleukin (IL)-2 and IL-4 demonstrated the largest ENDS user/nonuser difference. Compared with nonusers, salivary IL-2 and INFγ were elevated and IL-4 was decreased among ENDS users. Findings reveal dysregulation of salivary immune profiles toward a TH 1 phenotype in emerging adult ENDS users. There was a trend toward greater likelihood of persistent cough among ENDS users. Abstract: Though e-cigarette aerosol has been associated with altered lung cell function, few studies have examined the effects of use on immune response and respiratory symptoms. The purpose of this study was to examine if recent persistent cough or cytokine levels are related to Electronic Nicotine Delivery Systems (ENDS) use in college students. In April 2019, 61 undergraduate students at the University of Kentucky completed surveys and provided a salivary sample to evaluate cytokine levels (Interleukin (IL-) 2, 4, 6, 8, 10, 12, 13 and TNFα, INFγ), using quota sampling to obtain comparable numbers of ENDS users and non-ENDS users. Data analysis included chi-square tests and multivariable logistic and linear regression. All ENDS users reported JUUL as their primary product. ENDS users were more likely to be younger, use cigarettes and marijuana, and report a persistent cough. Controlling for cigarette and marijuana use, there was a trend toward greater likelihood of persistent cough among ENDS users. Compared with nonusers, salivary IL-2 and INFγ were elevated and IL-4 was decreased, controlling for cigarette and marijuana use. There was a trend toward lower IL-12p70 values among ENDS users with these covariates. Findings reveal dysregulation of salivary immune profiles toward a TH 1 phenotype in emerging adult ENDS users and short-term immune function may be dysregulated in young adult e-cigarette users.